Bone Health in School Age Children: Effects of Nutritional Intake on Outcomes - Abrams, Steven A. (Frontiers in Nutrition, 2021)
The maximum rate of bone mass accumulation is during early adolescence. As such, a focus on optimizing mineral nutrition in school age children, defined here as approximately 5 to 15 years of age, is crucial to minimize the risk of bone loss that occurs later in life leading to osteoporosis and fractures. Optimizing bone mass in this age group requires attention to an overall healthy diet including adequate calcium, phosphorus, magnesium, and vitamin D. Special concerns may exist related to children who follow a restricted diet such as a vegan diet, those with intolerance or allergies to dairy, and those with chronic health conditions including young adolescents with eating disorders. Public policy messages should focus on positive aspects of bone health nutrition in this age group and avoid strict guidance on the exact amount of calcium that should be in the diet. In this regard, dietary recommendations for minerals vary between North America and Europe and these are higher than the values that may be necessary in other parts of the world. The management of many children with chronic illnesses includes the use of medications that may affect their bone mineral metabolism. Routine lab testing for bone mineral metabolism including the serum 25-hydroxyvitamin D level is not indicated, but is valuable for at-risk children, especially those with chronic illnesses.